Risk Factors of Leptospirosis among Agricultural Workers in Southeast Asia: Literature Review - Wibowo, Ronggo Adi; Nurzakia, Wawa Najwa; Kirana, Meirany Sasitha; Wijaya, Yulia Arthemisia; Sekaryudha, Jasmine Ayumaharani; Rejeki, Dwi Sarwani Sri; Jayanti, Rosita Dwi (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
The agricultural sector is the primary source of livelihood for communities in Southeast Asia; however, these activities increase the risk of exposure to zoonotic diseases, particularly leptospirosis. Southeast Asia is one of the regions with the highest incidence of leptospirosis in the world. This literature review aims to identify risk factors for leptospirosis among agricultural workers in Southeast Asia. The search for research articles utilized three databases (Google Scholar, PubMed, and ScienceDirect) using a descriptive approach based on literature review and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A total of 9,800 articles were screened for duplicates, publication year (2016–2025), open access, English language, and analytical study design, leaving 459 articles. These articles were then screened based on exclusion criteria (review articles and those irrelevant to the keywords), resulting in 253 articles that met the inclusion and exclusion criteria. These articles were further reviewed based on relevant populations and outcomes, resulting in 10 articles to be included in the literature review. The findings of this study revealed variations in risk factors across countries, including the presence of livestock, the presence of waste in the work environment, and the habit of not using Personal Protective Equipment (PPE). Based on the findings, there is a publication gap in Southeast Asian countries regarding leptospirosis risk factors among agricultural workers, thus necessitating further research in other Southeast Asian countries. Keywords: Risk Factors, Leptospirosis, Farmers, Livestock Farmers, Planters, Southeast Asia